MODEL PENDIDIKAN AGAMA ISLAM INTEGRASI-INTERKONEKSI (HIKMAH dan WISDOM SEBAGAI VISI PENDIDIKAN MASA) - Boli, Mukdar; Tobroni, Tobroni; Fariadi, Fariadi (Universitas Muhammadiyah Mataram, 2024)
The integrated-interconnected Islamic Religious Education Model is needed so that there is no dichotomy of religious knowledge and general knowledge. because all scientific aspects require other scientific aspects to perfect each other. In order to understand each other, the various PAI models are therefore interrelated and complementary solutions. The integration-interconnection model of Islamic religious education will be successful if it is carried out with knowledge, experience and practice of Islamic values and accompanied by work intelligently, thoroughly and sincerely. This article begins with a thematic approach to the word